Objectification and Post-Traumatic Stress Disorder in Nina Iphechukwu’s Disowned - Anthonia, Eguvwebere Adanma (NIU Journal of Humanities, 2021)
Literary theories have sought to analyse and examine the ideologies inherent in the lives and thinking of the people. To this effect, Literature on trauma analyses some dark experiences of humans that illuminate the traumatic experiences of literary characters. This paper examines Objectification and Post Traumatic Stress Disorder (PTSD) in Daddy’s Little Girl , a story from Nina Iphechukwu’s Disowned . It examines childhood traumatic experiences and Post-Traumatic Stress Disorder in the selected character. This paper adopts a literary content analysis method and trauma theory. The theory charts a correlation between the experiences of the selected character and the effects of the traumatic events. The paper concludes that nightmares, mental breakdown, helplessness, lack of trust, and self-effacement can be read as symptoms of repressed childhood traumatic experiences. It concurs with Cvetkovich and Blooms’ assertion that trauma can be an external built-up of unpleasant events that affect the victim's psychological state which in turn affects the individual’s external actions in life.  Keywords: Objectification, Trauma, Post-Traumatic Stress Disorder (PTSD)